An Open-Label Study of Cranial Electrotherapy Stimulation on Behavioral Regulation in a Mixed Neurodevelopmental Clinical Cohort - Annie Brandes-Aitken; Molly Gerdes; Neil Hattangadi; Kevin A. Shapiro; Elysa J. Marco (Journal of Integrative Neuroscience, 2023)
Objective: Individuals with neurodevelopmental disorders often report disturbances in the autonomic nervous system (ANS)-related behavioral regulation, such as sensory sensitivity, anxiety, and emotion dysregulation. Cranial electrotherapy stimulation (CES) is a method of non-invasive neuromodulation presumed to modify behavioral regulation abilities via ANS modulation. Here we examined the feasibility and preliminary effects of a 4-week CES intervention on behavioral regulation in a mixed neurodevelopmental cohort of children, adolescents, and young adults. Methods: In this single-arm open-label study, 263 individuals aged 4–24 who were receiving clinical care were recruited. Participants received at-home CES treatment using an Alpha-Stim® AID CES device for 20 minutes per day, 5–7 days per week, for four weeks. Before and after the intervention, a parent-report assessment of sensory sensitivities, emotion dysregulation, and anxiety was administered. Adherence, side effects, and tolerance of the CES device were also evaluated at follow-up. Results: Results showed a 75% completion rate, an average tolerance score of 68.2 (out of 100), and an average perceived satisfaction score of 58.8 (out of 100). Additionally, a comparison between pre- and post-CES treatment effects showed a significant reduction in sensory sensitivity, anxiety, and emotion dysregulation in participants following CES treatment. Conclusions: Results provide justification for future randomized control trials using CES in children and adolescents with behavioral dysregulation. Significance: CES may be a useful therapeutic tool for alleviating behavioral dysregulation symptoms in children and adolescents with neurodevelopmental differences.